Respostas

A melhor resposta!
2014-04-20T00:06:14-03:00
Basta iguala a 0.
a) f(x) = 3x+18
3x+ 18 = 0
3x = -18
x = -6

b) f(x) =  x-17
x - 17 =0 
x = 17

c) f(x) =  5x-3
5x - 3 = 0
x = 3/5

d) f(x) = 4x
4x = 0
x = 0/4
x = 0
1 5 1
f(x)=3/2x-1/5
3x/2 -1/5 = 0
3x/2 = 1/5
3x = 2/5
x = 2/15
2014-04-20T00:11:29-03:00
a) f(x) = 3x + 18
3x + 18 = 0
3x = 0 - 18
3x = - 18
x = - 18 : 3
x = - 6
---------------------------------------------------
b) f(x) =  x - 17
x - 17 = 0
x = 0 + 17
x = 17
---------------------------------------------------
c) f(x) =  5x - 3
5x - 3 = 0
5x = 0 + 3
5x = 3
x = 3 : 5
x = 0,6
---------------------------------------------------
d) f(x) = 4x
4x = 0
x = 0 : 4
x = 0